PERCEPTION OF FEMALE DOCTORS REGARDING FACTORS LEADING TO CAREER DISCONTINUATION IN PAKISTAN: A CROSS-SECTIONAL SURVEY (The Research of Medical Science Review, 2025)
Objective: To explore the factors that lead to the discontinuation of careers among currently practicing female house officers (HOs) and residents (PGs). Method: This is a descriptive cross-sectional study on practicing female doctors including house officers and postgraduate residents currently working in Civil Hospital Karachi (CHK). Data were gathered using a self-administered questionnaire with close-ended questions. The study duration was 4 months, from July 2023 to October 2023. The questionnaire included the factors responsible for career discontinuation. Cumulatively, 369 participants completed the questionnaire, out of which 183 (49.6%) were house officers and 186 (50.4%) were postgraduate residents. After the process of data collection data was analyzed through SPSS version 25. Results: The factors responsible for discontinuing the careers include work-home imbalance (88.1%), prolonged working hours (79.9%), neglecting children (77.5%), hectic on-call schedules (72.1%), physical exhaustion (67.2%), difficulty getting days off (55.6%), and prolonged residency duration (53.1%). Conclusion: Career discontinuation often stems from work-home imbalance, long working hours, demanding on-call schedules, and physical exhaustion. Various studies carried out in Pakistan highlight these issues, underscoring the urgent need for solutions in developing countries like Pakistan to prevent this loss.